Calidad del agua destinada para fines recreativos del estero maculillo cantón quevedo, provincia de los ríos - Lara Mendoza, Edgar Jefferson (2015)
This research "Quality of water intended for recreational purposes estuary Maculillo Quevedo Canton, in the province of Los Rios" was conducted between the months of April and October, in which the following objectives: Identify the sources of pollution and social and environmental conditions of recreation site characteristics Maculillo estuary; Determine the water quality in the estuary Maculillo for recreational purposes; Propose a mitigation plan for the deterioration of water quality of the estuary Maculillo. For identification of pollution sources and their socio-environmental conditions survey was applied to people who use the estuary for recreational purposes as well as adjacent to the workers; and the use of photographic records and field visit. As for the determination of water quality for recreational purposes analysis as performed: fecal coliforms, pH, OD, which were carried out in the microbiology laboratory at the State Technical University of Quevedo, while the parameters organochlorine pesticides, organophosphorus pesticides carbamates, phenols, fats and oils were analyzed in an accredited laboratory "Group Chemical Marcos" city of Guayaquil, the same as they were compared with the maximum permissible limits of Ministerial Agreement 028, of which only fecal coliform does not meet current regulations. The proposed mitigation plan for the deterioration of water quality of the estuary Maculillo is made based on the results obtained in the analyzes and surveys of users who frequent this estuary.